Brittle-ductile transitions in polycrystalline tungsten - Giannattasio, A; Yao, Z; Tarleton, E; Roberts, S (2010)
The strain rate dependence of the brittle-to-ductile transition (BDT) temperature was investigated in notched and un-notched miniature bars made of high-purity polycrystalline tungsten and in notched bars of less-pure sintered material. The activation energy, EBDT, for the process controlling the BDT in pure tungsten was equal to 1.0 eV both in un-notched and notched specimens, though the brittle-ductile transition temperature, TBDT, was 40 K lower at each strain rate for the un-notched samples, indicating that the activation energy, EBDT, is a materials parameter, independent of geometrical factors. The experimental data obtained from pure tungsten are described well by a two-dimensional dislocation-dynamics model of crack-tip plasticity, which is also discussed. For sintered tungsten, EBDT was found to be 1.45 eV; TBDT at a given strain rate was higher than in the pure tungsten by 90 K, suggesting that the BDT in tungsten is very sensitive to impurity levels. © 2010 Taylor and Francis.